"This Was No Act of God:" Disaster, Causality, and Politics. Issue 1 (March 2015) - Dodds, Graham G.
<x xml:space="preserve">Abstract</x> This article explores the evolution of human understandings of putatively natural disasters in three respects. First, it contends that human conceptions of natural disasters have dramatically changed over time, from placing causality and responsibility with God and religion, to nature and science, to humanity and politics. Second, it tracks part of that broad development by examining how the legal category "Act of God" has become increasingly archaic and irrelevant in modern jurisprudence. Third, it outlines the implications of this development for more robust conceptions of human agency and politics, and it considers the causes of the changing conceptions of disaster.